Políticas públicas urbanas em Cuiabá – Mato Grosso : o papel do instrumental técnico de planejamento para a identificação de necessidades sociais e adoção de políticas públicas - Portela, André Luiz Santos (2014)
The city of Cuiabá , currently considered a regional metropolis , had in its history periods of ascendancy and ostracized for decades . had its greatest population growth , from the end of the 1970s and 1980s , it was mainly through the advent of government programs instituted by the Federal Government , the best known of the march to the West . The beginning of the urbanization of Cuiabá , the process was marked by the rise of several settlements , as well as other spontaneous or induced forms of occupation . This phenomenon caused the urbanized area increased, thus creating administrative problems for all agencies working nba organization and physical planning of the city . With the choice of city to be one of the venues of the World Cup in 2014 , Cuiabá happened to have a great real estate " boom " before making undervalued areas to begin to have a value much higher than in previous years . Due to dynamic economic and population growth in recent decades , the state represented by the municipal government , instituted several laws concerning the division of land use , as well as the characterization of the urban area of the municipality in accordance with the laws created . From this also control mechanisms and management of urban space were created , one of these instruments was the real estate cadastre , which despite having the collection of tribute bias , is important for the state role in the function of ordering your territory domain , described by the plots of land in existing urban core of the city . For Work , were considered the need to have two important ally for Territorial Multipurpose Cadastre issues of these modules joined and used in Brazil is that of Levy , mainly through the Tax Land Urban Land Property - property tax, which note up the registration presenting data accurately will bring greater benefits when it comes to storage. As the collection is not the only factor used to Register, the dissertation aims , beyond the issue of tax , identify the districts that have lower default rates and higher tax , if this issue is related to the existence of improvements public ( water supply , sewage treatment with , Asphalt , health centers ) , the survey was conducted in 8 districts of the city considering the higher delinquency and by administrative region . So that the objectives were achieved was carried out as a methodology to analyze the work and collection of secondary , primary and documentary data , methodological procedures were performed as exploratory studies and systematic observation , Business - in-place in certain neighborhoods for research , which were made photographic records and search for data / information in public files of the municipal government . For the compilation of the data were used in Excel and ArcGIS software to perform spatial analysis allowed the study performed . Partly as a result it was found that in the city neighborhoods necessarily have better infrastructure has a low property tax delinquencies , being more related this issue by location and interest that the State has for her , regarding the collection suggest that considers , income data and indices such as the Human Development units - HDI , to perform the calculation of the tax , given that the values measured for a given neighborhood may be outside the realm of household income which causes the default tax .